Teaching Standard Galician to Vernacular Speakers: Reflections and Strategies - Benavides da Vila, Xabier (Madrygal. Revista de Estudios Gallegos, 2024)
Most language planning models identify four steps: the selection and coding of a standard variety, its implementation in society and the functional development of the new variety (Haugen 1983: 275). The efforts aiming at revitalizing a minority language will only be successful if they count on the involvement of the community of its real and potential users. In this document we will analyze how the ideological principles behind the planning of the Galician language relate to those that underlie the tensions among the different language models. We will pay special attention to the relationship between traditional speakers and standard Galician, often influenced by the ideologies of standard language and purism. We must acknowledge that the competence in and the use of standard Galician is one of the keys that will determine the future of our language and, therefore, we will need to highlight the importance of the media and the educational system as the agents in charge of the implementation of this new variety. Finally, we will propose some general guidelines for the adoption of the critical awareness approach (Siegel 2006) in teaching practice. We firmly believe that introducing this perspective into the classroom will allow students to develop their competence in standard Galician by critically exploring the ideologies about languages and language models present in our society and establishing comparisons between their home variety or language and standard Galician. We will consider the main goal of our work to be achieved if we manage to bring into the debate the need to recognize the urge that the different profiles of users acknowledge each other so we can together, as a stronger community, towards the revitalization of our language.